Recent Advances in Solid-Phase Extraction (SPE) Based on Molecularly Imprinted Polymers (MIPs) for Analysis of Hormones - Anele Mpupa; Shirley Kholofelo Selahle; Boris Mizaikoff; Philiswa Nosizo Nomngongo (Chemosensors, 2021)
Steroid hormones are active substances that are necessary in the normal functioning of all physiological activities in the body, such as sexual characteristics, metabolism, and mood control. They are also widely used as exogenous chemicals in medical and pharmaceutical applications as treatments and at times growth promoters in animal farming. The vast application of steroid hormones has resulted in them being found in different matrices, such as food, environmental, and biological samples. The presence of hormones in such matrices means that they can easily come into contact with humans and animals as exogenous compounds, resulting in abnormal concentrations that can lead to endocrine disruption. This makes their determination in different matrices a vital part of pollutant management and control. Although advances in analytical instruments are constant, it has been determined that these instruments still require some sample preparation steps to be able to determine the occurrence of pollutants in the complex matrices in which they occur. Advances are still being made in sample preparation to ensure easier, selective, and sensitive analysis of complex matrices. Molecularly imprinted polymers (MIPs) have been termed as advanced solid-phase (SPE) materials for the selective extraction and preconcentration of hormones in complex matrices. This review explores the preparation and application of MIPs for the determination of steroid hormones in different sample types.